Tailoring beam profile and OAM spectrum in domain-engineered nonlinear photonic crystals - Xinyu Zhang; Hangyu Li; Shiqiang Liu; Yan Chen; Zhihan Zhu; Hui Liu; Shining Zhu; Xiaopeng Hu (APL Photonics)
Nonlinear frequency conversion provides a powerful tool to generate and manipulate structured light at new wavelengths. In this work, to meet the demands of applications such as high-capacity optical communications and high-dimensional entanglement generation, we use ferroelectric domain engineering to generate frequency-doubled light beams carrying orbital angular momentum (OAM) superposition states and with adjustable radial intensity distribution. Angular and radial phase modulations were introduced into the modulation function of the second-order nonlinear coefficient distribution of lithium tantalate nonlinear photonic crystals, achieving simultaneous tailoring of the OAM spectrum and the radial intensity profile of the second harmonic (SH) waves. As a representative example, we demonstrate the generation of a SH wave that carries a comb-like OAM spectrum, with the radial intensity distribution concentrating on a ring with a specific radius. In addition, the nonlinear photonic devices developed in this work feature polarization insensitivity and broadband characteristics.